Os efeitos da modernização conservadora na luta política e sindical dos trabalhadores no sudoeste goiano: o bonapartismo, a autocracia burguesa e o Partido dos Trabalhadores (1975 1982) - Santos, Fernando Silva dos (2010)
The goal of this master s degree dissertation is to analyze the possibilities and particularities of the workers organization facing the political domination of established traditional groups in Jataí, a city located in the southwest of Goiás, during the 70 s and 80 s. During this period, the concept of development was attached to the Idea of progress. The conservative modernization process attempted by the supervisors of the region s atrophic capital enabled the local bourgeoisie not only to dominate the government structures, but also provided the control over the workers organizations demonstrations right from the beginning of the power alternation. This situation happened in a bourgeoisie autocracy with a bonapartist aspect in its democratic transition phase. We tried to establish the connections between the logic of accelerated development, that is a true characteristic of the capitalism in its monopolist phase, and the influence of this situation in the development of the labour union and the Workers Party in the southwest of Goiás by applying a methodological approach of an immanent analysis proposal of the economy, politics, social and cultural relations of this region